Experimental comparison and numerical heat analysis of newly designed shell-and-tube heat exchanger with designed geometry at different baffle intervals: status of energy efficiency - FEYZİOĞLU, AHMET (My University, 2024)
Optimizing the performance of the heat exchanger to increase the heat capacity while reducing the pressure drop is determined as the most important design goal. Three main designs of heat exchangers are made according to parallel flow, counter flow and cross flow arrangement. The heat exchanger used here is chosen as a parallel flow heat exchanger. The aim of this study is to investigate heat transfer, the energy efficiency and thermal performance changes on the fluid behavior of varying baffle spacings at different flow rates in a parallel flow shell-and-tube heat exchanger. Water with a density of 976.1 kg/m3 was used as the fluid in the analyses. Other thermophysical properties of water are as follows: cp, 4191.5 J/kg °C; m, 0.000391 kg/m s; K, 0.665 W/m °C. It has been observed that the energy efficiency and thermal performance values of the fluid differ with the change of the baffle intervals Bd1 = 80 mm, Bd2 = 120 mm and flow rates between Fr1 = 0.1 kg/h and Fr100 = 10.0 kg/h used in the newly designed shell-and-tube heat exchanger.
Keywords: Sosyal ve Beşeri Bilimler; Sanat; İç Mimarlık; İnşaat Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Art; Interior Architecture; Civil Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sanat ve Beşeri Bilimler (AHCI); Mühendislik; Sanat ve Beşeri Bilimler; MİMARİ; MÜHENDİSLİK, İNŞAAT; Engineering, Computing & Technology (ENG); Arts & Humanities (AHCI); ENGINEERING; ARTS & HUMANITIES; ARCHITECTURE; ENGINEERING, CIVIL; İnşaat ve Yapı Mühendisliği; Fizik Bilimleri; Mimari; Genel Mühendislik; Civil and Structural Engineering; Physical Sciences; Architecture; General Engineering; baffle intervals; CFD; exchanger; fluid behavior